The value of innovation impacts on health, life quality, safety, and regulatory research - Farquhar, Irina; Summers, Kent; Sorkin, Alan L. (Emerald, 2007)
This book will present contributions by economists, systems developers, safety, health services, occupational and environmental health, and biomedical researchers in the fields of regulatory development, safety, quality assurance, health outcomes, occupational health, and biomedicine. The contributing research will explore the synergy of new science-based risk regulatory approaches, industry focus on manufacturing efficiencies and information technology and biogenetic innovations, and consumers demand for improved safety and quality of products, services, quality assurance, and transparency of information.The book investigates the impact of information technology, biogenetic, and pharmacological innovation on individuals quality of life, safety, individual and system health care utilization, occupational and environmental health and formulary decision making, and costs. It contains analyses of clinical and health outcomes resulting from innovative biopharmaceutical entities and delivery systems in the treatment of chronic conditions. It emphasises effective quality, regulatory system, and consistent science-based decision-making practices from private and public organizations and demonstrates regulatory issues affecting innovation and efficiency.
Keywords: Business & Economics -- Economics -- General.; Business & Economics -- Development -- Business Development.; Personal & public health.; Occupational -- industrial health & safety.; Personnel management.; elektronické knihy; electronic books